The craft of oblivion : forgetting and memory in ancient China - Galvany, Albert (State University of New York Press, 2023)
"Examines the intersections between forgetting and remembering in classical Chinese civilization"-- Provided by publisher.
Keywords: China -- Civilization -- To 221 B.C. -- Sources.; China -- Civilization -- 221 B.C.-960 A.D. -- Sources.; Chinese literature -- To 221 B.C. -- History and criticism.; Chinese literature -- 221 B.C.-960 A.D. -- History and criticism.; Philosophy, Chinese -- To 221 B.C.; Philosophy, Chinese -- 221 B.C.-960 A.D.; Memory.; Chine -- Civilisation -- Jusqu'à 221 av. J.-C. -- Sources.; Chine -- Civilisation -- 221 av. J.-C.-960 -- Sources.; Littérature chinoise -- Jusqu'à 221 av. J.-C. -- Histoire et critique.; Littérature chinoise -- 221 av. J.-C.-960 -- Histoire et critique.; Philosophie chinoise -- Jusqu'à 221 av. J.-C.; Philosophie chinoise -- 221 av. J.-C.-960.; HISTORY / Asia / China.; Chinese literature; Civilization; Memory; Philosophy, Chinese; China; To 960; Criticism, interpretation, etc.; Sources